Towards Achieving a Sustainable Lean Transformation: Measuring Tangible and Intangible Gains - Osman, Azim Azuan; Ahmad Nazif, Noor Kamar; Rahamaddulla, Syed Radzi (IGI Global, 2023)
Toyota Motor’s success as a global brand automobile manufacturer has inspired manufacturing organizations worldwide to pursue lean transformation. However, a lack of understanding of lean sustainability hampers their progress towards achieving true lean organization status like Toyota. Without proper measurement, the gains from lean improvements remain unknown, leading to inaccuracies in strategy deployment. This chapter aims to define sustainable lean transformation gains and propose indicators to measure them. Extensive literature review reveals the importance of tangible and intangible indicators. To validate the proposed measurements, a survey involving 7 lean experts and 92 practitioners was conducted. Data analysis utilized content validity index, inter-rater agreement, and measurement model analysis. The chapter concludes by suggesting research opportunities to enhance lean management knowledge.